2017
DOI: 10.3389/fpls.2017.00707
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Herbicides Targeting Aromatic and Branched Chain Amino Acid Biosynthesis Support the Presence of Functional Pathways in Broomrape

Abstract: It is not clear why herbicides targeting aromatic and branched-chain amino acid biosynthesis successfully control broomrapes—obligate parasitic plants that obtain all of their nutritional requirements, including amino acids, from the host. Our objective was to reveal the mode of action of imazapic and glyphosate in controlling the broomrape Phelipanche aegyptiaca and clarify if this obligatory parasite has its own machinery for the amino acids biosynthesis. P. aegyptiaca callus was studied to exclude the indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Dor et al [197] showed that the main mechanism by which ALS-inhibiting herbicides and glyphosate control P. aegyptiaca is direct inhibition of the enzymes ALS and EPSPS, which are present and active in the parasite tissues. Around the same time, a secondary effect of glyphosate action, inhibition of the translocation of phloemmobile solutes from the tomato to P. aegyptiaca, was indicated [198].…”
Section: Herbicidesmentioning
confidence: 99%
“…Dor et al [197] showed that the main mechanism by which ALS-inhibiting herbicides and glyphosate control P. aegyptiaca is direct inhibition of the enzymes ALS and EPSPS, which are present and active in the parasite tissues. Around the same time, a secondary effect of glyphosate action, inhibition of the translocation of phloemmobile solutes from the tomato to P. aegyptiaca, was indicated [198].…”
Section: Herbicidesmentioning
confidence: 99%
“…Imazethapyr is a systemic herbicide that belongs to IMI class of herbicides (Imidazole) that control weeds by reducing the level of branched‐chain amino acids—isoleucine, leucine, and valine—through the inhibition of acetolactate synthase (ALS), an enzyme common to the biosynthesis of these amino acids. Imazethapyr can control broomrape (Dor et al., 2017; García‐Torres & López‐Granados, 1991; Rubiales & Fernández‐Aparicio, 2012; Tan et al., 2005) and annual weeds (Cantwell et al., 1989).…”
Section: Introductionmentioning
confidence: 99%
“…DOI: http://dx.doi.org/10.5772/intechopen.105356 herbicides include imazamox, imazapic, imazaquin, imazethapyr, nicosulfuron, metsulfuron, triasulfuron, chlorsulfuron, rimsulfuron, prosulfuron, pyroxsulam, diclosulam, and flumetsulam. In a study conducted by Dor [16], the tissue culture of broomrape was found to be more sensitive to imazapic in which a concentration of 0.05μM significantly decreased the biomass and a concentration of 10μM caused blackening of died callus, which suggests that free amino acid content increased with the increased in the concentration of imazapic as shown in Figure 2.…”
Section: Amino-acid Synthesis Inhibitorsmentioning
confidence: 94%